Nuri Cergas Sdn Bhd / Ahmad Zaid Hazim Zainudin - Zainudin, Ahmad Zaid Hazim (UITM Cawangan Johor Kampus Pasir Gudang, 2015)
All students of Diploma in Civil Engineering are required to undergo Industrial Training for 8 weeks as part of their course subject to completed their course for the Diploma of Civil Engineering. The attachment will be during the 4th semester of their study. During the eight weeks period of training, students will be supervise and monitored their training by supervisors of the company. For my Industrial Training, my internship is at Nuri Cergas Sdn Bhd (NCSB) which located at Shah Alam , Selangor. It is an engineering contractor company in Civil and Structures. This company has been established since 1996.